2015
DOI: 10.1164/rccm.201408-1426oc
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Short-Acting β2-Agonists. A Novel Genome-Wide Significant Locus on Chromosome 2 near ASB3

Abstract: Rationale: b 2 -Agonists are the most common form of treatment of asthma, but there is significant variability in response to these medications. A significant proportion of this responsiveness may be heritable.Objectives: To investigate whether a genome-wide association study (GWAS) could identify novel pharmacogenetic loci in asthma.Methods: We performed a GWAS of acute bronchodilator response (BDR) to inhaled b 2 -agonists. A total of 444,088 single-nucleotide polymorphisms (SNPs) were examined in 724 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 41 publications
1
32
0
2
Order By: Relevance
“…Ethnic differences have been demonstrated in allergy-related GWAS [23] and will be the focus of future studies including larger non-European populations. Also, future larger GWAS will have increased power to target gene by environment interactions and directly clinically relevant phenotypes, such as response to medication [24•]. …”
Section: Introductionmentioning
confidence: 99%
“…Ethnic differences have been demonstrated in allergy-related GWAS [23] and will be the focus of future studies including larger non-European populations. Also, future larger GWAS will have increased power to target gene by environment interactions and directly clinically relevant phenotypes, such as response to medication [24•]. …”
Section: Introductionmentioning
confidence: 99%
“…The most significant results were subsequently replicated in an independent population of 439 adult asthmatics [16]. Three SNPs in one region in chromosome 2 were associated with BDR.…”
Section: Hypothesis-testingmentioning
confidence: 83%
“…Other technology released was the Sequencing by Oligo Ligation Detection in 2007 [ 48 ]. The platform employs fragmented and amplifi ed DNA samples by emPCR on which sequencing is performed b y ligation method.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…Supershift and competition assays revealed that C/EBPb and members of the Sp and GATA families are differentially bound at PTGDR promoter region containing the SNPs and that the different SNPs modify the binding [ 48 ]. In 2011, our group researched PTGDR in asthmatic patients.…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
See 1 more Smart Citation